Práticas discursivas e cuidado de si: a constituição de subjetividades de alunas do Programa Mulheres Mil na Escrita dos Mapas da Vida - Linhares, Francisco Fred Lucas (2019)
The Programa Mulheres Mil is a public policy that seeks to serve women in situations of social vulnerability, providing technical and professional training, as well as seeking to operate a process of self-modification in their student body. One of the strategies proposed by the Program for this process of transformation is the writing of the Map of Life. In this sense, understanding that the Thousand Women is inscribed as a device of self-technologies (FOUCAULT, 2014b) and of the production of subjectivities determined by discursive practices of a Culture of Self (FOUCAULT, 2014a, 2014b, 2017), this thesis aims to analyze that types of subjectivities are discursively constituted in the writing of the maps of the life of the students. The study, with a qualitative interpretative nature and socio-historical approach, is included in the field of Applied Linguistics (MOITA LOPES, 2004; 2013). Theoretical analytic devices of the Foucaultian discourse analysis (Foucault, 1984, 1988, 2006, 2009), Feminist Studies (RAGO, 2006, SCAVONE, 2006, SWAIN, 2006) and Language Studies. The results show that the elaboration of the subjectivities of these students is crossed by discursive practices whose effects of the senses translate aspects of the classic Culture of Self and also translate practices of freedom.